EVALUASI KUALITAS VISUAL LANSKAP WISATA PANTAI BALEKAMBANG DI DESA SRIGONCO, KABUPATEN MALANG - Budiyono, Debora; Soelistyari, Hesti Triana (http://arl-faperta.ipb.ac.id/, 2016)
Balekambang beach area has the potential of natural resources and high visual landscape either natural and man made.These conditions make Balekambang beach area become one of the objects and attraction destinations in Malang district for the local and foreign tourists. Aesthetic landscape visual is one of the driving factors of the area to be visited to release stress from routine work. However, the current conditions of the landscape arrangement of Balekambang tourism beach are not yet appropriate, so that visual potential has not been optimally utilized. Based on these conditions evaluation efforts of landscape visual quality of Balekambang tourism beach needed to be done. The main purpose of this research was to evaluate the landscape quality visual of Balekambang tourism beach in Srigonco village, Malang district. While the specific purpose of this research was to determine and to assess the visual quality of Balekambang beach tourism area by estimating the beauty and defining the beauty zone of Balekambang beach tourism area based on the perception of respondents. This research used a survey method. The analysis method used Scenic Beauty Estimation (SBE) and Semantic Differential (SD). The results showed that generally the visual quality of Balekambang beach is categorized as medium beauty. The zone of the medium beauty quality area was 17.12 ha (56.84%) of the total area. The zone of high beauty quality area was 4 ha (13.16%). While the zone of low beauty quality area was 9 ha (30%).